Physiological responses in males with and without spinal cord injury to recumbent synchronous versus seated asynchronous arm crank stress tests (Respuestas fisiológicas en hombres con y sin lesión medular al realizar pruebas de esfuerzo con ergómetros de - Guillermo R. Oviedo; Juan Mariano Alamo; Oscar A. Niño-Mendez; Noémie Travier; Jose L. Ventura; Carlos A. Soto-Montañez; Joan Vidal; Josep Medina; Casimiro Javierre (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. Introduction: Maximal oxygen uptake (VO2) may be one of the most important variables in the study of the responses of people with spinal cord injury (SCI) and without SCI to physical exercise. The results achieved during its assessment serve as a diagnostic and health indicator in clinical settings. Objective: this study aimed to investigate the physiological responses in males with and without SCI performing a maximal incremental test on an asynchronous arm crank ergometer (ACr) and on a recumbent synchronous handbike ergometer (HB). Methods: ten males with SCI and 11 able-bodied males (AB group) participated in this study. Two maximal graded exercise tests were performed, starting at 10 watts and increasing the workload by 10 watts every minute until exhaustion. Results: the AB group achieved lower workloads and absolute VO2 values than the SCI group during the HB test (all p < 0.05). The submaximal values of the relative VO2 peak and RER at workloads between 40-90 watts showed significant differences between SCI and AB on HB and ACr. Significant linear relationships between workload and relative VO2 peak were found during the HB test (p < 0.001). Conclusions: these findings demonstrate that there are different physiological responses between adults with and without SCI when performing maximal and submaximal arm-ergometry. Interestingly, higher VO2 peak and workloads were achieved by the SCI group. In addition, specific prediction equations derived from the current study can be used to calculate the relative VO2 peak in handbikers with and without SCI.